PERSEPSI MASYARAKAT KONTEMPORER TENTANG EKSISTENSI TUHAN DAN AGAMA - Marsono Marsono (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2020)
This Study discusses the perspectives of contemporary society to the existence of God and religion and its relation to practical life. The discussion uses philosophical approach or philosophy of divinity in order to obtain a through and fundamental understanding of the nature of faith and diversity of society today. The existence of God and religion has always incited discourses throughout the history of human kind. The unresolved debates spawning a variety of views are distintive one to another and even contradictory. This article based by fact indicated that, theologically, there are people embracing a theologycal there are people embracing atheology and religion only on a theoretical level but not on practical (practical atheism/secularism). There are, also people sheltering behind human inability or impossibility of knowing God (agnosticism) and exist people who even totally reject God and religion both theoretically and practically (atheism).Â